The Impact of Green Marketing on Employee Green Performance: A study on Green Banking Practices in an Emerging Economy - Ashraf, Aysha; Alzu’bi, Rama Mohammad; Imam, Hasina; Karim, Md. Mobarak; Ahmed, S M Saief Uddin; Debnath, Gouranga Chandra; Arie, Fitty Valdi; Fenyves, Veronika (Journal of Posthumanism, 2025)
The increasing concern about the impact of human activities on the environment has led to a heightened emphasis on the discipline of management science, specifically in employee’s performance. The most effective strategy to embracing sustainability should be closely interconnected with the environmental, economic, and social aspects of performance. Moreover, scholars have recently shown considerable interest in the domain of green marketing. The mutual contributions of employees are essential for a firm's success and sustainability, especially when the organization emphasizes sustainable development. This research finds to evaluate the influence of green marketing on the environmental performance of employees within Bangladesh's banking sector. This study is intended to enhance academic research and streamline the process of finding pertinent publications and conducting future investigations. Using structural equation modelling technique, this study employed PLS-SEM version 4 software to analyze the associations between the variables in our study. The model was built utilizing extensive data gathered from a survey done in Bangladeshi green financial institutions. This study discovered that businesses could utilize green marketing methods to influence the environmental performance of their employees.